2004
DOI: 10.1007/s11095-004-7676-4
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Biodistribution of Novel Aptamer Compositions

Abstract: We find that conjugation and chemical composition can alter fundamental aspects of aptamer residence in circulation and distribution to tissues. Though the primary effect of PEGylation was on aptamer clearance, the prolonged systemic exposure afforded by presence of the 20 kDa moiety appeared to facilitate distribution of aptamer to tissues, particularly those of highly perfused organs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
228
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 258 publications
(235 citation statements)
references
References 44 publications
(60 reference statements)
3
228
0
4
Order By: Relevance
“…This result is in accordance with previous studies which showed that aptamers are not able to cross the BBB passively [35][36][37]. There were no significant differences between the two HER2 aptamers and the negative control aptamer, except a significant increase in kidney uptake for the negative control aptamer, which may be related to the difference in nucleotide sequence and therefore difference in hydrophilicity.…”
Section: Tissue Biodistributionsupporting
confidence: 92%
“…This result is in accordance with previous studies which showed that aptamers are not able to cross the BBB passively [35][36][37]. There were no significant differences between the two HER2 aptamers and the negative control aptamer, except a significant increase in kidney uptake for the negative control aptamer, which may be related to the difference in nucleotide sequence and therefore difference in hydrophilicity.…”
Section: Tissue Biodistributionsupporting
confidence: 92%
“…To retard clearance and improve bioavailability, a cholesterol or polyethylene glycol moiety can be conjugated to one end of the aptamer. 6,7 Still, bioavailability may best be achieved not by making the aptamer drug circulate longer in the system but by increasing its avidity (binding capacity or apparent affinity for its target), which can be realized by multimerizing the aptamers in a controlled fashion. 8 The development of useful therapeutics requires testing in animals before human trials can be carried out, and aptamer development may stall if crossreactivity of the selected human aptamer sequence with the animal model of choice is poor.…”
Section: Prospectsmentioning
confidence: 99%
“…26,40 Second, the modification of the peptide by PEGylation may enhance nanoprobe hydrophilicity, reduce nonspecific binding, and thus improve bioavailability and clearance when used in vivo. 41,42 For in vivo imaging, Oyster-800 dye was chosen for its biocompatibility and high wavelength (∼800 nm) and because it has minimal tissue absorbance and background with improved fluorescence sensitivity. 43,44 The in vitro experiments demonstrate that the FPRtargeting nanoprobe has high affinity and can specifically bind to neutrophils.…”
Section: Discussionmentioning
confidence: 99%